2016
DOI: 10.1590/1807-1929/agriambi.v20n12p1083-1088
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and yield of ‘Gigante’ cactus pear cultivated with different spacings and organic fertilizer

Abstract: The objective of this study was to evaluate the levels of macronutrients in cladodes and yield of cactus pear, cv. ‘Gigante’, cultivated with different cattle manure doses and plant spacings. The experimental design was randomized blocks in 4 x 3 factorial, with three replicates. The treatments consisted of the combination of four doses of cattle manure (0, 30, 60 and 90 Mg ha-1 year-1) with three spacings (1.00 x 0.50, 2.00 x 0.25 and 3.00 x 1.00 x 0.25 m). The contents of macronutrients and dry matter produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 12 publications
(12 reference statements)
9
28
0
Order By: Relevance
“…. On the other hand, Donato et al (2016) obtained, at 600 DAP, overall mean of Ca extraction of 268.33 kg ha -1 for every 10 t ha -1 of dry matter. Souza (2015), in an experiment with NPK fertilization at 620 DAP, found overall mean Ca extraction of 175.50 kg ha -1 for every 10 t ha -1 of dry matter production.…”
Section: Calcium Concetration In Cladodesmentioning
confidence: 92%
See 4 more Smart Citations
“…. On the other hand, Donato et al (2016) obtained, at 600 DAP, overall mean of Ca extraction of 268.33 kg ha -1 for every 10 t ha -1 of dry matter. Souza (2015), in an experiment with NPK fertilization at 620 DAP, found overall mean Ca extraction of 175.50 kg ha -1 for every 10 t ha -1 of dry matter production.…”
Section: Calcium Concetration In Cladodesmentioning
confidence: 92%
“…Both helped to increase the content and availability of N in the soil and, consequently, led to the incremental absorption of N by the forage cactus. Donato et al (2016) studied the effects of different doses of approximately 131.65 kg ha -1 N for every 10 t ha -1 of dry matter. Souza (2015), in an experiment with NPK fertilization at 620 days after planting, found that the mean export of N was 177.88 kg ha -1 for every 10 t ha -1 of dry matter.…”
Section: Nitrogen Concentration In Cladodesmentioning
confidence: 99%
See 3 more Smart Citations